2008
DOI: 10.1088/0022-3727/41/19/195302
|View full text |Cite
|
Sign up to set email alerts
|

An energy-dependent photoemission study on line-shape analysis in determining the absolute coverage of metallic thin films

Abstract: Energy-dependent photoemission was measured to investigate the validity of the analysis of line shape in determining the absolute coverage of atomically flat, metallic thin films. The surface states of two Ag/Au(1 1 1) thin films with carefully controlled coverage of Ag were measured and analysed. Our results confirm that line-shape analysis is a valid procedure; the absolute error associated with this technique is within 0.1 ML, which makes the technique advantageous over other techniques to determine the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To justify the assumption, we consider two aspects. 18 Upton et al 8 suggested that layer-resolved quantum-well states on Pb/ Si͑111͒ could be analyzed to determine the absolute film thickness. Second, previous workers reported that the photo- Fig.…”
mentioning
confidence: 99%
“…To justify the assumption, we consider two aspects. 18 Upton et al 8 suggested that layer-resolved quantum-well states on Pb/ Si͑111͒ could be analyzed to determine the absolute film thickness. Second, previous workers reported that the photo- Fig.…”
mentioning
confidence: 99%
“…The amount of deposited Ag was calibrated with the layer-resolved surface state. 11,15 Deposition conditions were controlled with particular care to ensure that the same amount of Ag was deposited each time. Figure 1 shows typical results from photoemission measurements near the center of the surface Brillouin zone of Ag/Au͑111͒.…”
mentioning
confidence: 99%
“…The amount of deposited Ag was precisely determined on analyzing the layer-resolved surface state at a small Ag coverage. 11,15 Through counting layer by layer, we determined unequivocally the absolute thickness to which the QWS corresponds.…”
mentioning
confidence: 99%
“…Silver was evaporated from a Knudsen crucible; its rate of deposition was calibrated with the evolution of the Shockley states on Ag/Cu͑111͒. 8,11,12 To monitor the evolution of the sample surface, we recorded photoemission spectra during sample annealing. Figure 1 shows typical results from well ordered thin films of Ag on Cu͑111͒.…”
mentioning
confidence: 99%